Learning in the Family Every Day (7) (Journal of Parents and Teachers, 2025)
The article describes how reading is carried out, taking into account that through reading, one can access other lives and develop imagination. When discussing a classic, it is understood that it may present difficulties regarding linguistic, stylistic, or even content levels. Additionally, a selection of reading books is included, along with their respective summaries to provide examples.
Keywords: books; reading; lives; examples; levels